ВИКОРИСТАННЯ ЗЕМЕЛЬНО-РЕСУРСНОГО ПОТЕНЦІАЛУ ЛУГАНСЬКОЇ ОБЛАСТІ - Savchenko, T.G. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The state of the use of a land-resource potential of the Lugansk area is analyzed. Features and problems concerning the use of lands are revealed. Directions on improvement of the use of the land resources are defined.